Systematic Review of International Student Mobility in Higher Education - Cankaya, Ibrahim (European Scientific Journal, ESJ, 2023)
In this study, it is aimed to examine systematically the articles published in the Web Of Science database between 1997-2023 in the field of educational sciences and social sciences related to student mobility. Articles on international student mobility increased significantly after Covid-19. Articles on equal opportunities and Erasmus student mobility received the most citations. The most used keywords in the articles are higher education, education mobility and international students, while the least used keyword is distinction. Journal of Higher Education was the journal that publishes the most articles on the subject. Most articles were published in the field of educational research. International student mobility has been evaluated to a limited extent in terms of sociology, psychology and educational administration. In the published articles, the issue was generally evaluated within the framework of quality in education. The number of articles published on equality of opportunity in education was quite low.